Laparoscopic longitudinal pancreatojejunostomy and modified Frey's operation for chronic calcific pancreatitis. Issue 5 (24th June 2019) - Senthilnathan, P; Subrahmaneswara Babu, N; Vikram, A; Sabnis, S C; Srivatsan Gurumurthy, S; Anand Vijai, N; Nalankilli, V P; Palanivelu, C
Abstract: Background: Chronic pancreatitis is a debilitating disease presenting with pain, diabetes and steatorrhoea. Surgery offers better long-term pain relief than other interventions, but there is still uncertainty about the optimal surgical procedure and approach and a lack of long-term follow-up data in patients with chronic calcific pancreatitis selected for laparoscopic surgical treatment. Methods: This was an observational cohort study of patients who underwent laparoscopic surgery for chronic calcific pancreatitis between January 2006 and April 2017, and had completed a minimum follow-up of 1 year at a tertiary-care teaching institute. Eligibility for the laparoscopic approach was main duct diameter greater than 7 mm, absence of extensive head calcification, size of head less than 3·5 cm, absence of local complications, and ASA grade I or II status. The primary outcome variable was a reduction in pain score by 1 year. Secondary outcomes were hospital stay, complications, pain score at 3 and 5 years, and the development or progression of exocrine and endocrine insufficiency. Results: Some 57 patients were scheduled to undergo laparoscopic surgery for chronic pancreatitis: longitudinal pancreatojejunostomy (39), modified Frey's procedure (15) and pancreatoduodenectomy for suspicion of malignancy (3). The latter three patients were excluded from the analysis. Conversion to open surgery was needed in ten of the 57 patients (18 per cent). The mean(s.d.) age of the analysed cohort was 34·2(3·7) years and there was a predominance of men (34, 63 per cent). Adequate pain relief was achieved in 91, 89 and 88 per cent of patients at 1, 3 and 5 years of follow-up respectively. Conclusion: Laparoscopic surgical management of chronic calcific pancreatitis with longitudinal pancreatojejunostomy or modified Frey's procedure is feasible, safe and effective in selected patients for the relief of pain. Graphical Abstract: In this cohort of selected patients with chronic pancreatitis who underwent laparoscopic longitudinal pancreatojejunostomy or laparoscopic modified Frey's procedure, both procedures resulted in effective pain relief. Feasible with good results